Analisis perawatan Mesin Las Busur SMAW RHINO HT-200A dengan metode Failure Mode and Effect Analisys (FMEA) di PT. Sinergi Persada Nusantara - Kurniawan, Stefanus Aldy; Kardiman, Kardiman; Santoso, Deri Teguh (Universitas Muhammadiyah Metro, 2024)
PT Sinergi Persada Nusantara is a company engaged in manufacturing, fabrication and machining services. To support the production process in the industry, especially the automotive industry, heavy equipment, industrial special tools and consumer goods. Maintenance is all the activities needed to maintain the quality of equipment or machinery to keep it functioning properly and keep the facility or equipment always in a state of readiness. FMEA (Failure Mode Effect Analysis) is a method for evaluating the possibility of failure of a system, design, process or service to make handling steps. From the analysis of the RPN calculation on the RHINO HT-200A SMAW welding machine, the overall result is 817. This value exceeds the welding machine maintenance standards set with the overall RPN value must be below 400. A high RPN value indicates a low level of reliability on the tool.